Kitoka : an Alternative of Traditional String Instrument Instruction - Ihsan, Andi; Florentinus, Totok Sumaryanto (The Journal of Educational Development, 2018)
Kecapi is one of the nation's cultural products that is very popular in almost all communities in Indonesia. As a region that has various types of traditional harp (kecapi), South Sulawesi should be able to maintain the instrument in order to remain exist in the community. The government has made policies on local cultural arts in the form of curriculum by raising the local culture as one of the teaching materials that must be offered to the students. The process of traditional kecapi instruction in South Sulawesi is still using modern methods of music theory as a supporter of traditional kecapi instruction. The purpose of this study is to describe and analyze the development of kitoka as a form of innovation in order to answer the challenges related to the limitations of traditional string instruments especially in the learning process of music in South Sulawesi. In this research there are two types of data, i.e. primary data obtained from observation and direct interview with informants and secondary data as the supplement of the primary data obtained through literature study and documentation. The data that have been obtained through literature study, observation, interview and documentation are divided into categories and analyzed in order to be able to classify them and relate one class of data and the others. The result of this study is that the kitoka musical instrument is developed through innovation by looking at some weaknesses both in the procurement and the visual design of the traditional kecapi. This is certainly able to solve the problem of teaching kecapi in school without having to leave the traditional harp as a cultural product that must be preserved. Kitoka is part of a traditional harp developed on the basis of the needs of the people especially the popular community as it is today.